Ischemic signs on the post-resuscitation ECG in absence of STEMI is associated with lower survival. A COACT trial's sub-study. (14th October 2021) - Spoormans, E; Lemkes, J S; Janssens, G N; Van Der Hoeven, N W; Soultana, O; Jewbali, L S D; Dubois, E A; Meuwissen, M; Bosker, H A; Bleeker, G B; Vlachojannis, G J; Van Der Harst, P; et al.
Abstract: Background: The recently published Coronary Angiography after Cardiac arrest (COACT) trial found that urgent coronary angiography did not improve 90-day survival in out-of-hospital cardiac arrest (OHCA) patients without STEMI. The prognostic value of signs of ischemia on the ECG in absence of STEMI, is yet to be determined. Purpose: To assess whether ischemic ECG patterns such as ST-depression and T-wave inversion are predictors for survival after OHCA in patients without STEMI. Methods: In the COACT trial, patients with return of spontaneous circulation after OHCA with initial shockable rhythm and absence of ST-segment elevation were included. In this sub-study, the first post-resuscitation ECG recorded at the hospital was analysed for signs of ischemia. Ischemia was defined as ST-depression or T-wave inversion >1mm in ≥2 contiguous leads, or both. Primary endpoint was 90-day survival. Secondary endpoints included angiographic outcomes and left ventricular function assessed by cardiac magnetic resonance imaging or echocardiography. Results: In total, 552 patients were included in the COACT trial. For this sub-study, 510 OHCA-patients had an ECG available for assessment of whom 340 patients (66.7%) had signs of ischemia on the ECG and 170 patients (33.3%) were without signs of ischemia. Patients with signs of ischemia were significantly older (p=0.003) and more frequently had a history of CAD (p=0.009). Left ventricular ejection fraction was lower in those with signs of ischemia (p=0.007). The number of acute thrombotic occlusions did not differ between groups (p=0.34). Patients with signs of ischemia had a significantly worse 90-day survival compared to patients that showed no signs of ischemia (HR 1.51 (95% CI 1.08–2.12); log-rank p=0.02). Furthermore, larger ST-depression was found to be associated with worse survival (log-rank p=0.01). Neurologic injury was the most common cause of death and its incidence did not differ between the groups (p=0.77). Conclusion: Signs of ischemia in absence of STEMI on the post-resuscitation ECG is a predictor for worse survival. Furthermore, a correlation was found between the sum of ST-depression and lower survival rate. Funding Acknowledgement: Type of funding sources: Public Institution(s). Main funding source(s): Research grants of Netherlands Heart institue, Biotronic, AstraZeneca